Identification of a novel prognostic marker ADGRG6 in pancreatic adenocarcinoma: multi-omics analysis and experimental validation - Wu, Han; Shang, Jin; Bao, Yuanyan; Liu, Huajie; Zhang, Haoran; Xiao, Yaosheng; Li, Yangtaobo; Huang, Zhaozhang; Cheng, Xiaolei; Ma, Zixuan; Zhang, Wenqing; Mo, Pingli; et al. (Frontiers in Immunology, 2025)
BackgroundPancreatic adenocarcinoma (PAAD) ranks among the most lethal malignancies worldwide. Current treatment options have limited efficacy, underscoring the need for new therapeutic targets.MethodsThis study employed a multi-omics analytical framework to delve into the expression profiles and prognostic implications of ADGRG6 within the pan-cancer dataset of The Cancer Genome Atlas (TCGA) database, highlighting the prognostic value and potential carcinogenic role of ADGRG6 in PAAD, which was further validated using data from multiple PAAD cohorts in the Gene Expression Omnibus (GEO) database. To assess the role of ADGRG6 in the tumor microenvironment of PAAD, we evaluated immune infiltration using CIBERSORT, ssGSEA, xCell and Tracking Tumor Immunophenotype (TIP), and utilized single-cell sequencing data to explore cell-cell interactions. Further cellular and animal experiments, such as colony formation assay, transwell assay, western blot, real-time PCR, and tumor xenograft experiments, were used to investigate the effect of ADGRG6 on the proliferation, metastatic potential and immune marker expression of PAAD and the underlying mechanisms.ResultsADGRG6 emerged as a potential prognostic biomarker and a therapeutic target for PAAD, which was further corroborated by data extracted from multiple PAAD cohorts archived in the GEO database. Single-cell sequencing and immune infiltration analyses predicted the positive correlation of ADGRG6 with the infiltration of immune cells and with the interaction between malignant cells and fibroblasts/macrophages within the PAAD microenvironment. In vitro cell assays demonstrated that ADGRG6 promoted the proliferation, metastatic potential and immune marker expression of PAAD cells by increasing protein level of mutated p53 (mutp53), which activated a spectrum of gain-of-functions to promote cancer progression via the EGFR, AMPK and NF-κB signaling cascades. Furthermore, subcutaneous xenograft experiments in mice demonstrated that ADGRG6 knockdown substantially suppressed the growth of engrafted PAAD tumors.ConclusionsADGRG6 may serve as a novel prognostic marker and a therapeutic targets for PAAD, playing a crucial role in the proliferation, metastasis, and immune marker regulation of PAAD through elevating protein level of mutated p53.